Knowledge and Attitude of Malaysian Physiotherapists towards the Use of Ultrasound Imaging In the Physiotherapy Management Of Cervicogenic Headache - Dr Syed Abudaheer; Dr Esha Arora; Yu Chye Wah; Pavitra Sandaranggan (International Journal of Medical Toxicology and Legal Medicine, 2024)
Background: The study aims to explore Malaysian physiotherapists’ knowledge, attitudes, and utilization of Musculoskeletal Ultrasound Imaging in treating (CGH), identifying the limitation could potentially impede the widespread adoption of this imaging technique in clinical settings and lack of adequate training opportunities for physiotherapist in Musculoskeletal Ultrasound Imaging. Method: This was a cross-sectional study design consisting of an using an online survey of 303 Malaysian physiotherapists who were currently working in Malaysia. The survey was recruited through an orchestrated campaign utilizing popular social media platforms. Result: The study involved 303 participants, with 59.7% female and 40.3% male, showing a higher female participation rate. Participants were evenly spread across age groups, with the largest group aged 31-35 (30.4%). Most participants held a Degree (mean = 62%, standard deviation = 20.4%) or a Diploma (mean = 21.8%, standard deviation = 10.2%), indicating a highly educated sample. Only a small fraction had a Doctor of Philosophy degree (mean = 1.3%, standard deviation = 2.1%) or other credentials (mean = 0.3%, standard deviation = 1.5%). An analysis of knowledge levels showed that the majority (mean = 81.5%, standard deviation = 12.7%) scored below 60%, indicating a low level of knowledge in USI. Conversely, only a small fraction (mean = 4%, standard deviation = 3.2%) demonstrated high expertise. Conclusion: The study underscores a significant knowledge gap and varying attitudes towards USI among Malaysian physiotherapists. It emphasizes the importance of educational and infrastructural enhancements to foster its adoption in CHG management.